Synergistic effect of Euphorbia kansui stir-fried with vinegar and bile acids on malignant ascites effusion through modulation of gut microbiota - Dai, Shengyun; Zhou, Shikang; Ju, Yonghui; Yao, Weifeng; Tang, Yuping; Zheng, Jian; Ma, Shuangcheng; Zhang, Yi; Zhang, Li (Frontiers in Pharmacology, 2023)
Background: Toxic Euphorbia kansui (EK) is employed to treat malignant ascites effusion (MAE). EK stir-fried with vinegar (VEK) is conducted to reduce toxicity with preserved water-expelling effect. This was demonstrated to be correlated with gut microbiota. Thereinto, bile acids (BAs) have bidirectional relationship with gut microbiota. Therefore, the aim of this study is to explore whether BAs-mediated gut microbiota works in the water-expelling effect of VEK against MAE. Methods: The MAE rat model was established by intraperitoneal injection of Walker-256 tumor cells. A reliable simultaneous determination of fifteen bile acids in rat feces using UPLC-MS/MS was established and applied to analyze the fecal BAs in rats treated with VEK. The screened BA was then administrated to MAE rats with VEK. The water-expelling effect was evaluated using histopathological analysis, biochemical examinations, inflammatory factors in ascites, urine volume, ascites amount and intestinal aquaporin expression. The microbial composition was determined by 16S rDNA sequencing and contents of bile acids were finally measured. Results: VEK decreased the content of fecal deoxycholic acid (DCA), lithocholic acid (LCA) and taurocholic acid (TCA) while increasing the ursodeoxycholic acid (UDCA). VEK alleviated liver, stomach and intestinal injuries, oxidative damage and inflammation, which were further ameliorated with UDCA intervention. VEK alleviated MAE through increasing the fecal water content, urine volume and AQP3 protein expression and decreasing the urine Na+, K+, and Cl- levels. This was retained with the intervention of UDCA. UDCA and VEK regulated the disorder of BAs metabolism to a certain extent. Analysis of gut microbiota showed that VEK increased the abundance of Lactobacillus and decreased that of Prevotella_9 in MAE rats. Combined UDCA and VEK administration showed better modulation of microbiota structure than that treated with VEK alone, and the effect of this administration was closer to normal state. Conclusion: The water-expelling effect of VEK did not directly depend on the BA-mediated gut microbiota. But VEK and BAs had synergistic effect on malignant ascites effusion through regulating the gut microbiota. These results provided a scientific basis for the reasonable usage of VEK and the novel combination treatment strategy of VEK and UDCA.